THE ROLE OF THE SABILUL MUHTADIN TRADITIONAL ISLAMIC BOARDING SCHOOL IN FOSTERING THE MORALS OF THE COMMUNITY - Aat Royhatudin, Ahmad Hidayat, Ahmad Dimyati (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2021)
The emphasis on noble character (mahmudah) is very much focused on the Sabilul Muhtadien Islamic boarding school, because crimes often occur in the surrounding community. Through the role and contribution of traditional Islamic boarding schools, in this case, they have shown many advantages in producing generations of students and the surrounding community, including through coaching and learning, religious practices can shape behavior that manifests religious understanding in students and the surrounding community. The purpose of this study is to describe the state of Islamic boarding schools through recitations developed in the learning process that can form noble character (mahmudah) as well as analyze the process of good habits which can then be implemented in everyday life. Qualitative research methods with data collection, by collecting information from informants, both written and orally, researchers collect data by means of observation, in-depth interviews and documentation. Data analysis was carried out during data mining in the field and after data was collected. The results of this study found that the development of noble character which was implemented with the learning process in Islamic boarding schools could add to the improvement of religious life for children and the community, which was easy to do and manifested through ways of thinking, saying, and acting based on religious values, so that in real life it can be develop the ability of students from various faiths, worship and actuality, so that the practice of morals and synergistic